Personal Taxpayers ' Compliance Analysis with Regards to Tax Amnesty Policyprimary Tax Service Office in Medan City - Novien Rialdy (AIBPM Publisher, 2019)
KPP Pratama Medan Kota is one of the offices of government agencies in the field of taxation. KPP Pratama Medan City is currently implementing tax amnesty in order to support the acceptance of taxation for the country. The research was conducted using a descriptive research approach. The types of data in this study are qualitative and quantitative data. Data collection is done using documentation and interview methods. The data analysis technique used is using descriptive analysis. The purpose of this research is to find out how to apply the taxpayer compliance of private persons conducted by KPP Pratama Medan Kota, and to know the factors that are the cause of personal taxpayers do not follow Tax Amnesty. The results of research obtained during the study, namely, the implementation of taxpayer compliance of private persons conducted by KPP Pratama Medan Kota in accordance with the prevailing tax laws. Nevertheless, the implementation of taxpayer compliance of private persons conducted by KPP Pratama Medan Kota is still less effective, this is followed by still the minimum taxpayer of both registered private people still many have not participated in the TAX amnesty program.